Lathrolestes bipunctatus Bridgman 1886 ... - Reshchikov, Alexey (Zenodo, 2012)
Lathrolestes bipunctatus (Bridgman, 1886) Figs 58–61. Material: female, Russia, Kunashir, Golovin volcano, 24.vii.1973, D. Kasparyan; female, Russia, Kunashir, Uzhno-Kurilsk, 12.vii.1973, D. Kasparyan; 2females, Russia, Kamchatka, Kozyrevsk, deciduous., motley grass, 24.vii.1985, D. Kasparyan; female, Russia, Kamchatka, Kozyrevsk, Okhlonets Lake, 24.vii.1985, D. Kasparyan; female, Russia, Kamchatka, Kronotsky res., Uzon volcano, 09.viii.1985, I. Kerzhner; female, Russia, Chita reg., 70km NW Chita, Ivan-ozero Lake, larch forest, 03.vii.1975, D. Kasparyan. Distribution: Palearctic. ... : Published as part of Reshchikov, Alexey, 2012, Review and key to Russian Far East Lathrolestes (Hymenoptera, Ichneumonidae), pp. 1-32 in Zootaxa 3414 on page 25, DOI: 10.5281/zenodo.281927 ...